The Development of Professional Competencies in Ph.D. Candidates in Psychology: A Thematic Analysis Study - Sara Akbarzadeh; Amirahmad Shojaei; Fazlollah Ahmadi; Moluok Khademi Ashkzari (Kerman University of Medical Sciences, 2023)
Background: Psychology is one of the important disciplines dealing with mental health. Psychology students develop a set of professional competencies during their studies. The present study sought to explore the experiences of psychology students and assess the development of their professional competencies in the workplace.Methods: This qualitative study was conducted using a thematic analysis approach. The data were collected through 27 in-depth semi-structured interviews with 24 Ph.D. candidates in psychology who were completing their dissertations and 2 interviews with 2 professors of psychology. The data were analyzed using Braun and Clarke's six-step thematic analysis. The findings revealed the main themes, subthemes, and main categories. Lincoln and Guba's criteria were used to increase the trustworthiness of the findings.Results: The core theme identified in this study was professional competencies developed during academic studies. Besides, the five subthemes underlying professional competencies were creating and maintaining empathy, building a mutual understanding, enhancing confidentiality, being human and seeing others as human, and getting out of absolutism.Conclusion: The findings reported in the present study suggested that professional competencies are developed in psychology students during their studies according to their professional and clinical experience. Accordingly, providing adequate experiences can contribute to developing and promoting professional competencies in students.